Ethyl 2-{4-[(1,5-dibenzyl-2,4-dioxo-2,3,4,5-tetrahydro-1H-1,5-benzodiazepin -3-yl)methyl]-1H-1,2,3-triazol-1-yl}acetate - Jabli, H.; Rodi, Y.K.; Ladeira, S.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The reaction of 1,5-dibenzyl-3-propargyl-1,5-benzodiazepine-2,4-dione with ethyl azidoacetate in the presence of copper sulfate pentahydrate and sodium ascorbate leads to the formation of the title regioisomer, C(30)H(29)N(5)O(4), which features a phenylene ring fused with a seven-membered diazepinyl ring. The latter ring adopts a boat conformation (with the methyltriazolylacetate-bearing C atom as the prow and the fused-ring C atoms as the stern). The benzyl groups connected to the diazepinyl ring jprotrude from the sides; the methyltriazolylacetate substituent occupies an axial position.